Student's readiness for internship in FPA: KM Readiness Model Approach / Nur Wajihah Mohd Nawi ... [et al.] - Mohd Nawi, Nur Wajihah; Aziz, Nur Nabila Huda; Sahlan, Syahrizan; Zulkefli, Farahida; Awal, Asmah (UiTM Press, 2020)
According to Academic Information Management System (AIMS) of UiTM, it is compulsory for undergraduates of each faculty under UiTM to undergo a minimum of 8 weeks industrial training before graduation. Industrial training programme is a part of university's curriculum that can give opportunity for students to get exposed in the real workplace and professional practice. The students would be supervised by professional personnel in the certain period based on respective universities. In addition, the students need to follow all the procedures set by the faculty in order to pass the industrial training programme. The assessment of the student's performance would be assessed by the industry during this period of practical training.